Group A Streptococcal S Protein Utilizes Red Blood Cells as Immune Camouflage and Is a Critical Determinant for Immune Evasion - Igor H. Wierzbicki; Anaamika Campeau; Diana Dehaini; Maya Holay; Xiaoli Wei; Trever Greene; Man Ying; Jenna S. Sands; Anne Lamsa; Elina Zuniga; Kit Pogliano; Ronnie H. Fang; et al. (Cell Reports, 2019)
Summary: Group A Streptococcus (GAS) is a human-specific pathogen that evades the host immune response through the elaboration of multiple virulence factors. Although many of these factors have been studied, numerous proteins encoded by the GAS genome are of unknown function. Herein, we characterize a biomimetic red blood cell (RBC)-captured protein of unknown function—annotated subsequently as S protein—in GAS pathophysiology. S protein maintains the hydrophobic properties of GAS, and its absence reduces survival in human blood. S protein facilitates GAS coating with lysed RBCs to promote molecular mimicry, which increases virulence in vitro and in vivo. Proteomic profiling reveals that the removal of S protein from GAS alters cellular and extracellular protein landscapes and is accompanied by a decrease in the abundance of several key GAS virulence determinants. In vivo, the absence of S protein results in a striking attenuation of virulence and promotes a robust immune response and immunological memory. : Wierzbicki et al. show that S protein is a major group A Streptococcus (GAS) virulence factor that facilitates bacterial coating with lysed red blood cells to promote molecular mimicry, which increases virulence in vitro and in vivo. Removal of S protein reduces the abundance of multiple virulence factors and attenuates virulence. Keywords: Biomimetic Virulomics, S. pyogenes, group A Streptococcus, S protein, SPy_0802, virulence, systemic infection, multiplexed proteomics, tandem mass tags